PERKEMBANGAN BENTUK DAN FUNGSI PATUNG LORO BLONYO DALAM MASYARAKAT DI SURAKARTA - Ersnathan Budi Prasetyo (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
This article is the result of a study of the development of the formand function of the statue of loro blonyo in the Surakartacommunity. Themethod used for collecting data for the research included direct observation, a bibliographical study, and indepthinterviewswith cultural experts, academics, and the community using the loro blonyo statue. Fromthe results of theresearch it can be concluded that the loro blonyo statue is the symbol of a couple (aman and awoman), themanifestationof an imperceptible form, representing Dewi Sri and Sadana. In Javanese mysticism, this sacred statue is believed tosymbolize the embryo of the figure of a Javanese couple. The statue of loro blonyo is the product or result of the culture ofthe nobility, and as such, the rural Javanese community,who cannot afford to own such a statue, have transformed the loroblonyo statue into the formof amanten pari (rice wedding), alu lumpang (mortar and pestle), and ani-ani arit (knife forharvesting the rice). The statue of loro blonyo has undergone a change in form and function from a sacred to a profanesymbol.Keywords: loro blonyo,myth, sacred, profane.